Serum Albumin and Ca(2+) Are Natural Competence Inducers in the Human Pathogen Acinetobacter baumannii - Traglia, German Matias (Antimicrob Agents Chemother, 2016)
The increasing frequency of bacteria showing antimicrobial resistance (AMR) raises the menace of entering into a postantibiotic era. Horizontal gene transfer (HGT) is one of the prime reasons for AMR acquisition. Acinetobacter baumannii is a nosocomial pathogen with outstanding abilities to survive in the hospital environment and to acquire resistance determinants. Its capacity to incorporate exogenous DNA is a major source of AMR genes; however, few studies have addressed this subject. The transformation machinery as well as the factors that induce natural competence in A. baumannii are unknown. In this study, we demonstrate that naturally competent strain A118 increases its natural transformation frequency upon the addition of Ca(2+)or albumin. We show that comEA and pilQ are involved in this process since their expression levels are increased upon the addition of these compounds. An unspecific protein, like casein, does not reproduce this effect, showing that albumin's effect is specific. Our work describes the first specific inducers of natural competence in A. baumannii. Overall, our results suggest that the main protein in blood enhances HGT in A. baumannii, contributing to the increase of AMR in this threatening human pathogen.